2006
DOI: 10.1111/j.1467-9469.2006.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Using a Markov Chain to Construct a Tractable Approximation of an Intractable Probability Distribution

Abstract: Let π denote an intractable probability distribution that we would like to explore. Suppose that we have a positive recurrent, irreducible Markov chain that satisfies a minorization condition and has π as its invariant measure. We provide a method of using simulations from the Markov chain to construct a statistical estimate of π from which it is straightforward to sample. We show that this estimate is "strongly consistent" in the sense that the total variation distance between the estimate and π converges to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…This is the approach we use in our simulations. Further practical advice on simulating the split chain is given in Geyer and Thompson (1995), Hobert et al (2002), Hobert et al (2003) and Jones andHobert (2001, 2004).…”
Section: Regenerative Simulationmentioning
confidence: 99%
“…This is the approach we use in our simulations. Further practical advice on simulating the split chain is given in Geyer and Thompson (1995), Hobert et al (2002), Hobert et al (2003) and Jones andHobert (2001, 2004).…”
Section: Regenerative Simulationmentioning
confidence: 99%
“…The exact sampling algorithm considered here utilizes a mixture representation for π (Asmussen et al, 1992;Hobert et al, 2006;Hobert and Robert, 2004), however, we must first develop the split chain. The main assumption necessary is that X satisfies a one-step minorization condition, i.e.…”
Section: Exact Sampling Via a Mixture Distributionmentioning
confidence: 99%
“…The representation at (4) can be obtained from results in Asmussen et al (1992) by applying their methods to the split chain. Alternatively, Hobert and Robert (2004) obtain the representation when s(x) has the specific form εI C (x) and Hobert et al (2006) obtain the representation with the more general minorization shown here.…”
Section: A Mixture Representation Of πmentioning
confidence: 99%
See 1 more Smart Citation
“…, which have been implemented in several practically relevant statistical models; see e.g Doss and Tan (2013)Gilks et al (1998);Hobert et al (2006);Jones et al (2006);Jones and Hobert (2001);Roy and Hobert (2007).…”
mentioning
confidence: 99%